Judge Authority To Cancel The Notary Deed As Authentic Evidence - Moh Adib Aristyawan; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) to identify and explain the authority of a judge to cancel the notarial deed as authentic evidence 2) To identify and explain the condition of the cancellation of a notary and legal consequences of the cancellation of an authentic deed. This research method is using empirical juridical approach